Fibroblast culture on poly(L-lactide-co-epsilon-caprolactone) an electrospun nanofiber sheet - Jang, Bong Seok; Jung, Youngmee; Kwon, Il Keun; Mun, Cho Hay; Kim, Soo Hyun (POLYMER SOC KOREA, 2012)
Electrospinning has been used to make a nanofibrous matrix for vascular tissue engineering applications. The poly(L-lactide-co-E >-caprolactone) (PLCL) copolymer (50:50), which is biodegradable and elastic, was used to fabricate electrospun nanofiber sheets with a thickness of 20-50 mu m. The objective of this study was to investigate the behavior of fibroblast cells on the PLCL electrospun sheet. The cell proliferation on the PLCL electrospun sheet was evaluated. The cell morphology was observed using scanning electron microscopy. Several coating materials were evaluated to increase cell adhesion, including fibronectin, Type-I collagen, and gelatin. Among the coating materials tested, Type-I collagen gave the best result. Cell proliferation at all cell densities was tested steadily increase up to 3 weeks. Single side cell seeding and double side cell seeding were compared. During cell proliferation for 3 and 7 days, the single side cell seeding slowly increased, whereas rapid cell growth was observed for the double side seeding. We evaluated the mechanical properties of electrospun nanofiber scaffolds cultured with different cell volumes. In these experiments, a higher cell volume resulted in higher tensile strength and Young's modulus. Further studies are being conducted to design a functional tubular vascular scaffold with adequate mechanical properties and architecture to promote cell growth.
Keywords: DEGRADATION BEHAVIOR; IN-VITRO; SCAFFOLDS; FIBERS; CELLS